Study of Value-Added Soybean-Based Processed Products in Three Regencies of East Java Province - Hadi, Syamsul; Setya Rintyarna, Bagus; Dina Rizkina, Fitriana; Dina Rizkina, Fitriana; Martha Muliasari, Risa; Nurina Aulia, Anisa (Journal of Rural Development, 2023)
The soybean stock availability in Pasuruan, Jember and Banyuwangi regencies of East Java Province has experienced a very worrying development in the past few years due to decline in production by above 29 per cent. This has implications for the sustainability of the tofu and soybean cake (tempeh craft). Along with the limited availability of raw material, i.e. soybean, the production costs tend to reduce the added value. The purpose of this study was to analyse the added value, the relationship of soybean commodity stock availability and added value, the factors that influence profit, and the added value of the tofu & tempeh craft. Descriptive correlative method with survey and non-probability sampling techniques as well as data collection techniques through in-depth interviews were used for this study. For data analysis, Hayami method, Pearson Product Moment Correlation, and Cobb-Douglas Model Multiple Regression were used. The results of this study revealed that i) the average value added of tofu & tempeh products is IDR 8,608.09 per kilogram of raw materials with an added value ratio of 47.11 per cent; ii) there is a fairly strong positive relationship between the variable stock availability of raw materials and the added value of tofu & tempeh products, iii) the variable of the amount of production, and the price of production have a significant effect on the profit of the tofu & tempeh craft at the real level α1 per cent; and 4) variable amount of soybean raw material significantly influences the added value of tofu & tempeh products at the real level of 1 per cent.